Sprachwitz in den Texten österreichischer Kabarettisten - Utri, Reinhold (Wydawnictwo Naukowe UAM, 2011)
Jokes are a part of our culture. The aim of this essay is the analysis and systematization of cabaret texts of well-known Austrian cabaret artists. The witty sketches are a complex phenomenon and consist of language puns (manipulation, bizarre fantasy, imitation of other people, current topics) and of non-verbal elements like music, movement and mimic art.
Language pun in the texts of Austrian cabaret artists
Keywords: cabaret; jokes; language puns; sketches; cabaret texts